"In‐loop" carbonylation—A simplified method for carbon‐11 labelling of drugs and radioligands. (21st January 2020) - Ferrat, Mélodie; Dahl, Kenneth; Halldin, Christer; Schou, Magnus
Abstract: Transition‐metal mediated carbonylation with 11 C‐labelled carbon monoxide ([ 11 C]CO) is a versatile method for introducing 11 C ( t 1/2 = 20.3 min) into drugs and radioligands for subsequent use in positron emission tomography (PET). The aim of the current study was to perform the 11 C‐carbonylation reaction on the interior surface of a stainless‐steel loop used for high performance liquid chromatography (HPLC). In the experimental setup, cyclotron produced 11 C‐labelled carbon dioxide ([ 11 C]CO2 ) was converted to [ 11 C]CO by reduction over heated Molybdenum and swept into an HPLC loop pre‐charged with the appropriate reaction mixture. Following a 5 min reaction, the radiochemical purity (RCP) and the trapping efficiency (TE) of the reaction mixture was determined. After optimization, [ 11 C] N ‐Benzylbenzamide was obtained in quantitative radiochemical yield (RCY) following a 5 min reaction at room temperature. The methodology was further applied to label [ 11 C]benzoic acid (RCP≥99%, TE>91%), [ 11 C]methyl benzoate (RCP≥99%, TE>93%) and [ 11 C]phthalide (RCP≥99%, TE>88%). A set of pharmaceuticals was finally radiolabelled using non‐optimized conditions. Excellent yields were obtained for the histamine‐3 receptor radioligand [ 11 C]AZ13198083, the oncology drug [ 11 C]olaparib and the dopamine D2 receptor radioligand [ 11 C]raclopride, whereas a moderate yield was observed for the high‐affinity dopamine D2 receptor radioligand [ 11 C]FLB457. The presented "in‐loop" process proved efficient for diverse 11 C‐carbonylations, providing [ 11 C]amides, [ 11 C]esters and [ 11 C]carboxylic acids in moderate to excellent RCYs. Based on the advantages associated with performing the radiolabelling step as an integrated part of the purification system, this methodology may become a valuable addition to the toolbox of methodologies used for 11 C‐carbonylation of drugs and radioligands for PET. Abstract : A new "in‐loop" methodology was developed to simplify palladium‐mediated carbonylations with [ 11 C]carbon monoxide. The methodology proved to be useful in generating 11 C‐labelled amides, esters and carboxylic acids. Given its simplicity, efficiency and compatibility with automation, this methodology may become a valuable addition to the toolbox of methodologies used for 11 C‐carbonylation of drugs and radioligands for PET.